2022
DOI: 10.1111/1759-7714.14669
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib for treating rhabdomyosarcoma in adult patients with poor performance status: A case report

Abstract: Rhabdomyosarcoma (RMS) is a common soft tissue sarcoma usually observed in children. However, RMS rarely occurs in adults. The prognosis of adult RMS is poor and a standard chemotherapy regimen has not yet been established. Herein, we report the case of a 60-year-old Japanese woman with primary anterior mediastinal alveolar RMS (T3N0M0, stage III). The tumor increased aggressively despite first-line treatment with doxorubicin (60 mg/m 2 every 3 weeks for 1 cycle) and second-line treatment with eribulin (1.4 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…7 Data related to adjuvant chemotherapy for primary cardiac rhabdomyosarcoma remain limited due to its rarity, however, a recent study found pazopanib hydrochloride to be beneficial, especially in cases with previous ineffective treatments or poor performance status. 8…”
Section: Discussionmentioning
confidence: 99%
“…7 Data related to adjuvant chemotherapy for primary cardiac rhabdomyosarcoma remain limited due to its rarity, however, a recent study found pazopanib hydrochloride to be beneficial, especially in cases with previous ineffective treatments or poor performance status. 8…”
Section: Discussionmentioning
confidence: 99%